THE INFLUENCE OF CUSTOMER RELATIONSHIP MANAGEMENT, RELATIONSHIP MARKETING, AND SERVICE EXCELLENCE ON CUSTOMER ATTENTION MEDIATED BY CUSTOMER TRUST AT RADEN INTEN II AIRPORT LAMPUNG : A CASE STUDY AT RADEN INTEN II AIRPORT LAMPUNG - Afif Kurnia Anakis; Rahyono; Ayu Nursari (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the effect of Customer Relationship Management (CRM), Relationship Marketing (RM), and Service Excellent (SE) on Customer Attention with Customer Trust as a mediating variable among service users at Raden Inten II Airport, Lampung. The research method used is quantitative with a survey approach. The research sample consisted of 400 respondents drawn from the airport passenger population using a non-probability sampling technique and Slovin's formula. Data collection was carried out through Likert-scale questionnaires distributed offline and online. Data analysis was performed using SPSS software, which included instrument quality tests, classical assumption tests, multiple linear regression, hypothesis testing (t-test and F-test), and the Sobel Test to measure the significance of the mediating variable. The results showed that partially and simultaneously, CRM, RM, and SE had a positive and significant effect on Customer Trust and Customer Attention. In addition, the tests proved that Customer Trust significantly mediated the effect of CRM, RM, and SE on Customer Attention. Relationship Marketing was found to be the variable that provided the most dominant direct contribution. Overall, this study concludes that customer trust has a central role and serves as a vital psychological mechanism that strengthens relational marketing strategies and service quality in shaping sustainable customer attention.